2021
DOI: 10.1038/s41598-021-03000-9
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning prediction of antiviral-HPV protein interactions for anti-HPV pharmacotherapy

Abstract: Persistent infection with high-risk types Human Papillomavirus could cause diseases including cervical cancers and oropharyngeal cancers. Nonetheless, so far there is no effective pharmacotherapy for treating the infection from high-risk HPV types, and hence it remains to be a severe threat to the health of female. Based on drug repositioning strategy, we trained and benchmarked multiple machine learning models so as to predict potential effective antiviral drugs for HPV infection in this work. Through optimiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Each pair of proteins is split into several residues, with two residues of two proteins in the same cluster interacting. In terms of performance, they achieved an accuracy value of 60%, which is generally lower than those of the SVM and ANN methods, due to the difference in the amount of information available on the proteins ( Ahmed, 2020 ; Jonathan et al, 2021 ; Lin et al, 2021 ).…”
Section: Methods Based On the Machine Learning Algorithmmentioning
confidence: 89%
See 1 more Smart Citation
“…Each pair of proteins is split into several residues, with two residues of two proteins in the same cluster interacting. In terms of performance, they achieved an accuracy value of 60%, which is generally lower than those of the SVM and ANN methods, due to the difference in the amount of information available on the proteins ( Ahmed, 2020 ; Jonathan et al, 2021 ; Lin et al, 2021 ).…”
Section: Methods Based On the Machine Learning Algorithmmentioning
confidence: 89%
“…; X m ,Y), where X{X1,X 2, X 3, ….,X m } is the m-dimensional input variable and Y is the output variable taking {0,1}. As input, this method can take either protein interaction datasets or genomic interaction datasets ( Jansen et al, 2003 ; Alashwal, Deris and Othman, 2009 ; Lin et al, 2021 ). In the end, the classifier gives a binary response, a zero indicating the interaction is not verified, and a one when there is a potential interaction.…”
Section: Methods Based On the Machine Learning Algorithmmentioning
confidence: 99%
“…In a 2021 study, 57 antiviral HPV protein interactions were successfully predicted from the 864 antiviral HPV protein associations ( Lin H. H. et al, 2021 ). The investigators used data from DrugBank, Drugs@FDA, PubChem, Uniprot, and Therapeutic Targets, which collected data databases on antiviral drugs and their associated Targets.…”
Section: Application Of Artificial Intelligence In Hpv Detectionmentioning
confidence: 99%
“…Regarding the combination of HDAC inhibitors with antivirals to eradicate HPV infections, hitherto, there are no HPV-specific antiviral agents approved for clinical use, however, machine learning and therapeutic repositioning are emerging strategies to identify antiviral molecules. Lin et al (2021) identified 57 antiviral drugs with potential interaction with E1, E2, E4, E5, E6, E7 L1, and E8^E2 ( Lin et al, 2021 ). However, the effectiveness of these candidates and their impact on epigenetic alterations have not yet evaluated.…”
Section: Epigenetic Therapy and Chemopreventionmentioning
confidence: 99%